Imaging of Pseudomonas aeruginosa infection with Ga-68 labelled pyoverdine for positron emission tomography. Issue 1 (December 2018) - Petrik, Milos; Umlaufova, Eva; Raclavsky, Vladislav; Palyzova, Andrea; Havlicek, Vladimir; Haas, Hubertus; Novy, Zbynek; Dolezal, Dalibor; Hajduch, Marian; Decristoforo, Clemens
Abstract Pseudomonas aeruginosa is an increasingly prevalent opportunistic pathogen that causes a variety of life-threatening nosocomial infections. Novel strategies for the development of new antibacterial treatments as well as diagnostic tools are needed. One of the novel diagnostic strategies for the detection of infection could be the utilization of siderophores. Siderophores are low-molecular-weight chelators produced by microbes to scavenge essential iron. Replacing iron in siderophores by suitable radiometals, such as Ga-68 for positron emission tomography (PET) imaging, opens approaches for targeted imaging of infection. Here we report on pyoverdine PAO1 (PVD-PAO1), a siderophore produced byP. aeruginosa, labelled with Ga-68 for specific imaging ofPseudomonas infections. PVD-PAO1 was labelled with Ga-68 with high radiochemical purity. The resulting complex showed hydrophilic properties, low protein binding and high stability in human serum.In vitro uptake of68 Ga-PVD-PAO1 was highly dependent on the type of microbial culture. In normal mice68 Ga-PVD-PAO1 showed rapid pharmacokinetics with urinary excretion. PET imaging in infected animals displayed specific accumulation of68 Ga-PVD-PAO1 in infected tissues and better distribution than clinically used18 F-fluorodeoxyglucose (18 F-FDG) and68 Ga-citrate. Ga-68 labelled pyoverdine PAO1 seems to be a promising agent for imaging ofP. aeruginosa infections by means of PET.